Bioengineering application using co-cultured mesenchymal stem cells and preosteoclasts may effectively accelerate fracture healing. (February 2019) - Hou, Weiduo; Ye, Chenyi; Li, Weixu; Zhang, Wei; He, Rongxin; Zheng, Qiang
Abstract: Fracture non-union is the most challenging complication following fracture injuries. Despite ongoing improvements in the surgical technique and implant design, the treatment efficacy of fracture non-union is still far from satisfactory and currently there is no optimal solution. Of all of the methods used for the treatment of non-union, bone tissue bioengineering using scaffolds and mesenchymal stem cells (MSCs) is the most widely studied and has emerged as a promising approach to address these challenges. However, there are several critical limitations, such as the low survival rate of MSCs under an inflammatory, ischemic environment. Accumulating studies have demonstrated that preosteoclasts not only play a role in the remodeling of the callus, but also participate in the entire process of fracture repair. The close crosstalk between preosteoclasts and MSCs stimulates the recruitment, proliferation, and differentiation of osteoblasts and improves the osteogenic differentiation of MSCs. With no in vivo study reported thus far, we hypothesize that the administration of preosteoclasts together with MSCs at a certain ratio may effectively accelerate fracture healing and provide a new and promising therapeutic strategy for the clinical management of fracture non-union.